2021
DOI: 10.1111/fwb.13781
|View full text |Cite
|
Sign up to set email alerts
|

Microbial consortia in an ice‐covered high‐altitude lake impacted by additions of dissolved organic carbon and nutrients

Abstract: 1. High-altitude lakes are sentinels of change. Anticipated increases in inputs of dissolved organic carbon (DOC) from catchments in high-altitude lakes could affect planktonic interactions, especially if inputs occur during the winter ablation phase.However, the responses of plankton communities to added DOC interacting with nutrients during this period are still not well understood.2. We sampled under-ice water and used a multifactorial experimental design to investigate the DOC effect on planktonic organism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 61 publications
2
7
0
Order By: Relevance
“…These two results suggest limitation primarily by nutrients and co-limitation by C of bacteria. This pattern of co-limitation has already been observed in high-latitude lakes (Dorado-García et al 2014) and in Lake Cordes in the ice-covered period (Dory et al 2021). Both the present study and the previous one found evidence that bacterioplankton in Lake Cordes were co-limited by nutrients and C from April to August.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These two results suggest limitation primarily by nutrients and co-limitation by C of bacteria. This pattern of co-limitation has already been observed in high-latitude lakes (Dorado-García et al 2014) and in Lake Cordes in the ice-covered period (Dory et al 2021). Both the present study and the previous one found evidence that bacterioplankton in Lake Cordes were co-limited by nutrients and C from April to August.…”
Section: Discussionsupporting
confidence: 89%
“…In these ecosystems, the highest proportion of mixotrophs is usually observed after snowmelt, because the mixotrophic strategy is advantageous under ice‐cover, when nutrients and light are limiting factors (Waibel et al 2019). A recent microcosm study on Lake Cordes demonstrated that under‐ice species of cryptophytes were able to develop in the dark, likely by ingesting bacterial prey (Dory et al 2021). Conversely, other studies positioned cryptophytes toward the autotrophic end of an increasing trophic state gradient (Saad et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the perception of winter as an inactive period has been challenged (Hampton et al, 2017), and many studies (e.g. Felip et al, 2002;Bashenkhaeva et al, 2015;Ardyna et al, 2020;Dory et al, 2021;Hazuková et al, 2021; Abstract Little is known on the dynamics of underice phytoplankton communities. We investigated phytoplankton communities in the upper (0-20 m) and lower (30-35 m) layer of oligotrophic Lake Tovel, Brenta Dolomites (Italy) over 6 years during summer and under ice.…”
Section: Introductionmentioning
confidence: 99%